2021
DOI: 10.3201/eid2704.204200
|View full text |Cite
|
Sign up to set email alerts
|

Increased SARS-CoV-2 Testing Capacity with Pooled Saliva Samples

Abstract: We analyzed feasibility of pooling saliva samples for severe acute respiratory syndrome coronavirus 2 testing and found that sensitivity decreased according to pool size: 5 samples/pool, 7.4% reduction; 10 samples/pool, 11.1%; and 20 samples/pool, 14.8%. When virus prevalence is >2.6%, pools of 5 require fewer tests; when <0.6%, pools of 20 support screening strategies .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 11 publications
4
39
0
Order By: Relevance
“…In this study we evaluated a sample pooling strategy for mass screening of groups of individuals, using saliva as sampling material instead of NPSs. The rational for this study relied in the fact that sampling of saliva is considered as reliable as, but easier than sampling with NPS, chiefly for some categories of patients/individuals ( Pasomsub et al, 2021 ; Watkins et al, 2021 Takeuchi et al, 2020 ) . Also, pooling of samples is a strategy that decreases costs and times for laboratory analysis, and proved helpful to screen large numbers of asymptomatic people ( Lohse et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we evaluated a sample pooling strategy for mass screening of groups of individuals, using saliva as sampling material instead of NPSs. The rational for this study relied in the fact that sampling of saliva is considered as reliable as, but easier than sampling with NPS, chiefly for some categories of patients/individuals ( Pasomsub et al, 2021 ; Watkins et al, 2021 Takeuchi et al, 2020 ) . Also, pooling of samples is a strategy that decreases costs and times for laboratory analysis, and proved helpful to screen large numbers of asymptomatic people ( Lohse et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of pool sampling of saliva are several for SARS-CoV-2 systematic and repeated monitoring: i) saliva samples can be self-collected by individuals, even by children, without any stimulation and without rinsing the mouth before sample collection, simply placing the bibula strip inside the buccal cavity for a few seconds; ii) bibula strips ensures an adequate adorbption of saliva in a few seconds, preventing the use of invasive swabs and decreasing the sampling times, and guarantees processing of up to 30 salivary samples in few mL of medium; iii) no restriction on timing or food intake are required for saliva collection ( Nagura-Ikeda et al, 2020 ). Recent studies have already evaluated the saliva pooling strategy, replacing the use of the NPS for sampling ( Lohse et al, 2020 ; Pasomsub et al, 2021 ; Watkins et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We industrialized the OS process in the form of an "all-in-one" kit simplifying extraction of the biological liquid (figure 4) and presently intend to clinically validate the performance of this sampling method with the pooling technique [54] for mass screening.…”
Section: Discussionmentioning
confidence: 99%
“…Workflows for whole-genome SARS-CoV-2 sequencing begin with sample collection, typically from discarded clinical diagnostic specimens. While nasopharyngeal (NP) swabs are still considered as the 'gold standard' for SARS-CoV-2 diagnostic testing, we have shown that saliva is a sensitive 6,7 and stable 8 sample type, which can be reliably self-collected 9 , for the detection of SARS-CoV-2 RNA by RT-qPCR diagnostic assays in the absence of RNA extraction 10 . As saliva is increasingly being used in diagnostic testing programs, we sought to determine if saliva samples can be used to generate high-quality SARS-CoV-2 genomes.…”
Section: Introductionmentioning
confidence: 99%